XI. studentská vědecká konference Katedry českého jazyka a literatury 14. března 2019 - Žvaková, Kateřina (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2019)
Title in English: XI. Student Scientific Conference of the Czech Language and Literature Department This collection presents the contributions of the students of Master's and doctoral study programmes to the Student Scientific Conference held on 14/03/2019. Kateřina Žvaková deals with conversation analysis in Communication strategy tools used by the guests in GEN (documentary series), application of didactics is presented in Pavlína Zouharová's Commercials in Czech Language Teaching of sixth-through-ninth graders in primary schools. Radim Ošmera focuses on the teaching of non-native Czech speakers in his Czech phonetics/phonology principles applied by non-native speakers of the Czech language, Veronika Tinková presents Worksheet design for Czech language for bilingual sixth-through-ninth graders and Věra Šimková presents Adapted reading exercises in the Czech-speaking environment. Miroslav Jindra deals with Methodology of research into children's theatre audiences through a case study of a production of Vinnetou. The collection is concluded by literary scientific contributions from Kateřina Tesařová with her Death motifs found in the early poetic works of Jiří Karásek ze Lvovic and J.H. Krchovský and Ondřej Pechník's Reflection of the Israeli-Palestinian conflict in Tomáš Kolský's work.